High‐Density RNA Microarrays Synthesized In Situ by Photolithography. Issue 46 (19th October 2018) - Lietard, Jory; Ameur, Dominik; Damha, Masad J.; Somoza, Mark M.
Abstract: While high‐density DNA microarrays have been available for over three decades, the synthesis of equivalent RNA microarrays has proven intractable until now. Herein we describe the first in situ synthesis of mixed‐based, high‐density RNA microarrays using photolithography and light‐sensitive RNA phosphoramidites. With coupling efficiencies comparable to those of DNA monomers, RNA oligonucleotides at least 30 nucleotides long can now efficiently be prepared using modified phosphoramidite chemistry. A two‐step deprotection route unmasks the phosphodiester, the exocyclic amines and the 2′ hydroxyl. Hybridization and enzymatic assays validate the quality and the identity of the surface‐bound RNA. We show that high‐density is feasible by synthesizing a complex RNA permutation library with 262144 unique sequences. We also introduce DNA/RNA chimeric microarrays and explore their applications by mapping the sequence specificity of RNase HII. Abstract : The nucleotides have turned : Using photolithography, phosphoramidite chemistry and a new set of base‐sensitive monomers, mixed‐base RNA microarrays can now be synthesized in situ. RNA arrays fabricated at high‐density can accommodate up to about 780 000 different sequences inside a small, approximately 1.5 cm 2 wide synthesis area. The concept is illustrated with the synthesis of all possible 9‐nt long sequence permutations.